Do mobile phones, economic growth, bank competition and stability matter for financial inclusion in Africa? - Tough Chinoda; Farai Kwenda (Cogent Economics & Finance, 2019)
The lower levels of financial inclusion and severe financial inclusion gaps in Africa motivates the investigation of whether mobile phones, economic growth, bank competition and stability matter for financial inclusion. Data from 49 countries for the periods 2004-2016 were collected and analysed using a five-variable panel structural vector autoregressive model. There was evidence to show that financial inclusion responds positively and significantly to shocks in bank competition, economic growth, mobile phones and bank stability. However, the results reveal that all the variables respond to one standard deviation shock in financial inclusion, suggesting that while the variables matter for financial inclusion, they also require financial inclusion for their effective operation. Hence, the conclusion is that financial inclusion plays a central in the effective running of economies.
Keywords: G2; F65; G21; L5; 330; financial inclusion; bank competition; bank stability; economic growth; panel structural vector autoregressive model